Distribution of distinct subsets of circulating T follicular helper cells in Kawasaki disease - Meng Xu; Yanfang Jiang; Jinghua Wang; Deying Liu; Shaofeng Wang; Huanfa Yi; Sirui Yang (BMC Pediatrics, 2019)
Abstract Background Kawasaki disease (KD) is an acute febrile vasculitis that primarily affects children. Previous studies have shown that both innate and adapt immune systems are involved in the immunopathogenesis of KD. The following study analyzes the distribution of the subsets of Circulating T follicular helper cells (cTfh cells) in KD patients with and without coronary artery lesions (CALs). Methods Twenty KD patients and fifteen healthy sex- and age- matched children were enrolled. Patients were divided into two groups depending on CALs. Blood samples were collected respectively before and after intravenous immunoglobulin (IVIG) administration. Circulating Tfh cells were categorized into three subsets by flow cytometry including cTfh1 (CXCR3 + CCR6-), cTfh2 (CXCR3-CCX6-) and cTfh17 (CXCR3-CCR6+) cells in circulating CD3 + CD4 + CXCR5 + CD45RA- T cells. Cytometric bead arrays were used to analyze the level of IFN-γ, IL-4 and IL-17A. Results We found that frequency of cTfh2 cells was significantly elevated in KD patients before IVIG administration with low expression of cTfh1 cells, where the ratio of cTfh2 + cTfh17/cTfh1 significantly increased. Levels of IFN-γ, IL-4 and IL-17A in KD were significantly higher compared to controls. Further analysis showed that cTfh1 cells were negatively correlated with serum CRP, whereas cTfh2 cells were positively correlated with serum CRP and ESR. Comparison of different groups showed that frequency of cTfh1 cells in CALs+ group were significantly lower compared to CALs- group. In contrast, cTfh2 cells in CALs+ group significantly increased. After IVIG administration, frequency of cTfh2 cells and the ratio significantly decreased while the frequency of cTfh1 cells significantly increased. Meanwhile, all levels of cytokines decreased. Conclusions Our data demonstrated that cTfh1 and cTfh2 cells participate in the pathogenesis of KD, and that the two subsets might be associated with CALs.